A bi-proxy reconstruction of Fontainebleau (France) growing season temperature from A.D. 1596 to 2000 - N. Etien; V. Daux; V. Masson-Delmotte; M. Stievenard; V. Bernard; S. Durost; M. T. Guillemin; O. Mestre; M. Pierre (Climate of the Past, 2008)
In this paper, we develop a new methodology to estimate past changes of growing season temperature at Fontainebleau (northern France). Northern France temperature fluctuations have been documented by homogenised instrumental temperature records (at most 140 year long) and by grape harvest dates (GHD) series, incorporated in some of the European-scale temperature reconstructions. We have produced here three new proxy records: δ18O and δ13C of latewood cellulose of living trees and timbers from Fontainebleau Forest and Castle, together with ring widths of the same samples. δ13C data appear to be influenced by tree and age effects; ring widths are not controlled by a single climate parameter. By contrast, δ18O and Burgundy GHD series exhibit strong links with Fontainebleau growing season maximum temperature. Each of these records can also be influenced by other factors such as vine growing practices, local insolation, or moisture availability. In order to reduce the influence of these potential biases, we have used a linear combination of the two records to reconstruct inter-annual fluctuations of Fontainebleau growing season temperature from 1596 to 2000. Over the instrumental period, the reconstruction is well correlated with the temperature data (R2=0.60). This reconstruction is associated with an uncertainty of ~1.1°C (1.5 standard deviation), and is expected to provide a reference series for the variability of growing season maximum temperature in Western Europe. Spectral analyses conducted on the reconstruction clearly evidence (i) the interest of combining the two proxy records in order to improve the power spectrum of the reconstructed versus observed temperature, (ii) changes in the spectral properties over the time, with varying weights of periodicities ranging between ~6 and ~25 years. Available reconstructions of regional growing season temperature fluctuations get increasingly divergent at the interannual or decadal scale prior to 1800. Our reconstruction suggests a warm interval in the late 17th century, with the 1680s as warm as the 1940s, followed by a prolonged cool period from the 1690s to the 1850s culminating in the 1770s. The persistency of the late 20th century warming trend appears unprecedented.